EFEKTIFITAS TERAPI BERMAIN (MEWARNAI) PADA ANAK USIA PRASEKOLAH YANG MENGALAMI HOSPITALISASI DI RUMAH SAKIT ZAINAB PEKANBARU - HERNITATI HERNITATI; MAGDALENA MAGDALENA; HELDA HASAN (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2015)
The purpose of this study was to determine the effectiveness of play therapy in preschool children who experienced hospitalization. This research was conducted in hospitals Zainab Pekanbaru in October – December 2015 Number of respondents 20 children. The study design used was a pre experimental one group pretest posttest design. Samples were taken with a sampling technique used saturated or total population. Variables measured in this study is the impact of using questionnaires hospitalization. Based on the analysis of data it can be seen that there is the effectiveness of play therapy with hospitalization with p value = 0.01 (p <0.05). The conclusion of this study the presence of the effectiveness of play therapy on hospitalization in the nursing room Zainab hospital Riau Province. Suggestions to further research may add a larger sample again with more specific inclusion criteria in order to get maximum results.